The Effectiveness of Cultural Center Management by the West Sumatra Provincial Government - Yunita Yunita; M. Fachri Adnan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by the suboptimal management of the West Sumatra Provincial Cultural Building as a regional asset and public facility. The identified problems include damaged building facilities, inadequate maintenance, limited supporting infrastructure, insufficient safety aspects, and facility services that have not fully supported arts and cultural activities. This study aims to analyze the effectiveness of the management of the West Sumatra Provincial Cultural Building and to identify the factors affecting its effectiveness. This research employed a descriptive qualitative approach. Informants were selected using purposive sampling and consisted of the Secretary of the West Sumatra Provincial Culture Office, the Head of the Cultural Park Technical Implementation Unit (UPTD), management staff, visitors, and members of arts communities. Data were collected through observation, interviews, and documentation and analyzed using Duncan's organizational effectiveness theory, which includes goal achievement, integration, and adaptation. The findings indicate that the management of the West Sumatra Provincial Cultural Building has not been fully effective. This is reflected in the damaged facilities, limited maintenance budget, inadequate infrastructure, and suboptimal services provided to building users. Factors influencing management effectiveness include human resources, facilities and infrastructure, budget availability, and regulations or policies. Therefore, improvements are required through better facility maintenance, stronger coordination among stakeholders, budget optimization, and policy enhancement to ensure that the Cultural Building functions optimally as a center for arts and cultural activities